The impact of asset transfer on livelihoods of the ultra poor in Bangladesh - Ahmed, Akhter; Rabbani, Mehnaz; Sulaiman, Munshi; Das, Narayan C. (International Food Policy Research Institute, 2009)
Bangladesh’s progress in economic growth and extensive social protection interventions have contributed to a reduction in the headcount poverty rate of around 1.5 percentage points a year since the early 1990s. This progress in poverty reduction is, however, little comfort: the overall incidence of poverty persists at a high level. The most startling consequence of widespread poverty is that a quarter of the country’s population — 37 million people — cannot afford an adequate diet. Chronically underfed and highly vulnerable, they remain largely without assets (other than their own labor power) to cushion lean-season hunger or the crushing blows of illness, flooding, and other calamities. These extreme poor are a group that straddles the outer limits of human survival. The need for targeted interventions to improve food security and livelihoods of the extreme poor therefore remains strong.